Concentration, size distribution and dry deposition of amines in atmospheric particles of urban Guangzhou, China. (December 2017) - Liu, Fengxian; Bi, Xinhui; Zhang, Guohua; Peng, Long; Lian, Xiufeng; Lu, Huiying; Fu, Yuzhen; Wang, Xinming; Peng, Ping'an; Sheng, Guoying
Abstract: Size-segregated PM10 samples were collected in Guangzhou, China during autumn of 2014. Nine amines, including seven aliphatic amines and two heterocyclic amines, were detected using a gas chromatography-mass spectrometer after derivatization by benzenesulfonyl chloride. The total concentration of the nine amines (Ʃamines) was 79.6–140.9 ng m −3 in PM10 . The most abundant species was methylamine (MA), which had a concentration of 29.2–70.1 ng m −3 . MA, dimethylamine (DMA), diethylamine (DEA) and dibutylamine (DBA) were the predominant amines in the samples and accounted for approximately 80% of Ʃamines in each size segment. Two heterocyclic amines, pyrrolidine (PYR) and morpholine (MOR), were detected in all samples and had average concentrations of 1.14 ± 0.37 and 1.89 ± 0.64 ng m −3, respectively, in particles with aerodynamic diameters < 3 μm. More than 80% of Ʃamines were found in particles with diameters <1.5 μm, indicating that amines are mainly enriched in fine particles. All amines exhibited a bimodal distribution with a fine mode at 0.49–1.5 μm and a coarse mode at 7.2–10 μm. The maximum contributions of amines to particles (0.21%) and amines-N to water-soluble organic nitrogen (WSON) (3.1%) were found at the sizes < 0.49 μm. The maximum contribution of amines-C to water-soluble organic carbon (WSOC) was 1.6% over the size range of 0.95–1.5 μm. The molar ratio of Ʃamines to ammonium ranged from 0.0068 to 0.0107 in particles with diameters <1.5 μm, and the maximum ratio occurred in the smallest particles (diameter< 0.49 μm). The average dry deposition flux and velocity of Ʃamines in PM10 were 7.9 ± 1.6 μg m −2 d −1 and 0.084 ± 0.0021 cm s −1, respectively. The results of this study provide essential information on the contribution of amines to secondary organic aerosols and dry removal mechanisms in urban areas. Highlights: Size-resolved particulate amines were first characterized in the Pearl River Delta region, China. ƩAmines exhibited a predominant occurrence in the size fraction between 0.49 and 0.95 μm. The contribution of amines-N to WSON decreased with increasing particle size. The Ʃamines/ammonium molar ratio ranged from 0.0068 to 0.0107 in PM1.5 with a maximum at < 0.49 μm. Dry deposition fluxes of amines were dominated by fine particles within PM10 .